The Influence of Social Media Marketing and Electronic Word of Mouth (E-WOM) on Purchase Intention Through Trust in Indibiz Products in the Telkom Yogyakarta and Southern Central Java Area - Afifah Nuraghnia Kusumadewi; Retno Widowati (Politeknik Siber Cerdika Internasional, 2026)
Background: The digitalization of business services in Indonesia has boosted social media marketing (SMM) and e-WOM adoption among SMEs in the B2B telecommunications sector. However, trust as a link between SMM, e-WOM, and purchase intention for products like Indibiz remains underexplored. Objective: This study examines the impact of SMM and e-WOM on purchase intention for Indibiz through consumer trust, focusing on SMEs in the Telkom Yogyakarta Jateng Selatan area that use social media, are aware of Indibiz, but have not subscribed. Methods: This study uses a quantitative explanatory approach with purposive sampling, collecting 208 valid responses from 283 questionnaires via Google Forms. Data were analyzed using SEM-PLS with SmartPLS 4.0, including outer model tests (validity, reliability) and inner model analysis (path coefficients, bootstrapping, R²). Results: All seven hypotheses were supported. SMM positively influenced trust (β = 0.287, t = 3.42, p < 0.01) and purchase intention (β = 0.198, t = 2.21, p < 0.05). e-WOM positively influenced trust (β = 0.602, t = 7.15, p < 0.001) and purchase intention (β = 0.231, t = 2.64, p < 0.01). Trust significantly mediated both relationships (SMM→Trust→PI: β = 0.130; e-WOM→Trust→PI: β = 0.272). The model explained 73.1% of purchase intention variance (R² = 0.731). Conclusion: Trust mediates the relationship between digital marketing signals and B2B purchase intention in Indonesian telecommunications SMEs. Practitioners should focus on trust-building content strategies and manage e-WOM credibility to convert prospects into Indibiz subscribers. Future research should explore other regions and platforms.